Research-based instructional strategies in a flipped principles of microeconomics classroom. (March 2020) - Cosgrove, Sarah B.; Olitsky, Neal H.
Abstract: Principles of economics students often struggle to move beyond memorization of key terms and simple application of concepts to higher order thinking, such as evaluation and concept transfer. This higher order thinking is necessary for students to answer fundamental questions in economics. The primary advantage of the blend and flip format is that students can achieve low levels of learning, memorization of terms, and mastery of simple applications of concepts on their own before meeting for a face-to-face class. Previous research confirms that students in flipped-blended classes show larger gains in learning than students in moderately-blended classes. However, the gains we find are modest compared to those reported in related research in the math and science disciplines, which use research-based teaching practices, proven in the cognitive science literature. We determine the effects of using research-based instructional strategies on student learning in principles of microeconomics courses. Specifically, after controlling for a number of key background variables, we test whether students in flipped-blended classes who learn with research-based strategies in face-to-face classes are capable of applying knowledge and skills better than their counterparts in flipped-blended classes who are assigned practice problems similar to those on exams during face-to-face classes. Our findings indicate that students exposed to RBIS show significantly greater learning gains than students in the control group, and that these gains are most prevalent in the later part of the semester.